Anode Biofilm Formation With Applied External Voltage - Koltysheva, Dina; Shchurska, Kateryna; Kuzminskyi, Yevhenii (Innovative Biosystems and Bioengineering, 2023)
Background. The formation of an exoelectrogenic biofilm in a microbial fuel cell (MFC) is an important stage, because it affects later on current generation by the system. The fermented residue after methanogenesis as an inoculum contains not only exoelectrogenic microorganisms, but also methanogens, which reduce the productivity of MFC. The use of current allows the formation of a biofilm enriched with exoelectrogenic microorganisms. Objective. The purpose of our study was to establish the parameters of MFC under periodic application of external voltage. Methods. A two-chamber H-type MFC with a salt bridge between the chambers was used for the study. The anolyte was stirred with a magnetic stirrer for 4 h a day and a 3V voltage was simultaneously applied to create selective conditions for exoelectrogenic biofilm growth. Results. The application of external voltage stimulated the increase in the current and voltage of the MFC. With the periodic application of an external voltage, the MFC current increased to 788 ± 40 mA for the MFC with a resistor and without load. After disconnection and discharge, the MFC current dropped to 189 ± 10 mA for the MFC without load and to 154 ± 8 mA for the MFC with a resistor, respectively. Under the conditions of MFC operation without applying external voltage, the current was 960 ± 50 mA for MFC with an open circuit and 672 ± 35 mA for MFC with a closed circuit when a resistor is connected. For all MFC, the current gradually decreased over time. MFC demonstrated capacitive behaviour: after accumulating charge for 4 h, a discharge from 622 ± 30 mV to 462 ± 23 mV was observed. Microscopy showed fouling of the anode. Since the fermented residue after methanogenesis is mixed consortium, the anodic biofilm was also mixed consortium enriched with different species of exoelectrogens. Conclusions. Periodic application of external voltage allowed to increase the current by 17% and double the voltage compared to MFC without external voltage supply. However, after disconnecting the external voltage source, the MFC gradually discharged, that is, the current and voltage decreased. The maximum value of the current of the MFC with an open circuit was 22% more than the MFC with a closed circuit.